THE IDEA OF BUILDING A LEGAL SOCIETY THROUGH EDUCATION AND UPBRINGING IN THE SOCIO-LEGAL VIEWS OF THE JADIDS - Mukhitdinova Fiyuza Abdurashidovna; Mukhiddinova Dilyora Sherzodovna (Journal Park Publishing, 2025)
The article examines the socio-legal concept of the Jadid movement, focusing on the role of education and upbringing in building a just and law-based society. The Jadids viewed education as a legal and civic institution, central to shaping responsible citizens. Through the establishment of modern schools, development of textbooks, and promotion of civic values, they sought to foster an enlightened and lawful community. This study also draws a comparative analysis with Turkey and Germany, demonstrating how the Jadids adapted global educational experiences to local realities. The paper further explores how modern Uzbekistan under President Shavkat Mirziyoyev continues the Jadids’ mission through large-scale reforms in education, innovation, and youth development.
Keywords: Jadidism, education, civic consciousness, legal culture, Uzbekistan reforms, comparative legal studies, Fitrat, Behbudi, Mirziyoyev, modernization.